Effect of Brachytherapy vs. External Beam Radiotherapy on Sexual Function in Patients With Clinically Localized Prostate Cancer: A Meta-Analysis - Xie, Xiaodu; Zhang, Yuanfeng; Ge, Chengguo; Liang, Peihe (Frontiers in Cell and Developmental Biology, 2022)
Abstract: Purpose: The aim of this study is to compare the effect of brachytherapy (BT) vs. external beam radiotherapy (EBRT) on sexual function in patients with localized prostate cancer (PCa). Methods: Data were retrieved from the PubMed, Cochrane Library, Embase, China National Knowledge Infrastructure (CNKI), and Wanfang Database until March 4, 2021. Analysis was performed by using RevMan 5.4.1. The main clinical outcomes were the Prostate Cancer Symptom Indices (PCSI) scale and the Extended Prostate Cancer Index Composite (EPIC) scale scores for sexual function. A meta-analysis was performed to calculate standardized mean differences (SMD) and their 95% confidence interval (CI). This study has undergone PROSPERO registration (No.: CDR42021245438). Results: Among the 962 studies retrieved, eight prospective cohort studies met the inclusion criteria covering a total of 2,340 patients, including 1,138 treated with BT alone and 1202 treated with EBRT alone. The results demonstrated that BT was to some extent advantageous over EBRT in overall sexual function scores in patients with localized PCa during the immediate post-treatment period (SMD=-0.09, 95%CI: -0.18～-0.01, p=0.03), but this difference was not detectable at 3 months (SMD = -0.07, 95% CI: -0.18 to 0.05, p=0.25), 12 months (SMD =-0.01, 95% CI: -0.21 to 0.20, p=0.96) and 24 months (SMD=-0.09, 95% CI: -0.20 to 0.01, p=0.09) after treatment. Conclusion: Our analysis showed that BT showed a short-term advantage over EBRT in terms of sexual function in patients with localized PCa but this difference diminished over time, though the conclusion needs to be further verified by longer-term follow-up study.